Can South Africa afford to become Africa's first welfare state? - Thurlow, James (International Food Policy Research Institute, 2002)
This paper assesses the economy-wide impact of implementing and financing a universal or basic income grant (BIG) in South Africa. The various financing scenarios suggested by the proponents of the grant are presented, and these are compared using an applied general equilibrium model for the South African economy. The results indicate that the required changes in direct and indirect tax rates needed to finance the grant without increasing the government deficit are substantially higher than currently predicted. Furthermore, the alternative of reducing government recurrent expenditure to finance the BIG will undoubtedly undermine other government policy objectives. The paper therefore proposes a shift in the current debate, away from determining which of the individual financing options is preferable, towards an acknowledgement that a 'balanced' approach is likely to provide the only feasible scenario. Furthermore, the impact of the grant on economic growth is found to hinge on its ability to enhance factor productivity. These results suggest that the possibility of South Africa becoming the continent's first welfare state is as likely to rest with the macroeconomic impacts of financing the grant, as with the ability of the grant to address the country's prevailing poverty. This was also published as FCND Discussion Paper 139.